Sistem Pendukung Keputusan Kelayakan Nasabah Peminjam Menggunakan Metode COPRAS Berbasis Website - Murni, Ira; Ikhwan, Ali (Jurnal Algoritma, 2025)
In the financial industry, assessing customer eligibility for loans is a necessary process to avoid bad credit risks. This study offers the implementation of Complex Proportional Assessment (COPRAS) for customer eligibility. This study contributes to the development of a decision support system that improves the efficiency of microloan eligibility analysis. A decision support system is a framework or intelligent tool that enables decision makers to make decisions based on alternatives, criteria, and weights. The COPRAS method is useful for analyzing and determining the differences between several alternatives based on predetermined criteria. The final results show that Wiji Muliyani ranks first with the highest score of 100. This score was obtained from manual calculations and the system. The system also works well, as proven through black-box testing and usability testing using the System Usability Scale (SUS) method, which showed an average score of 95, meaning that the system is very good and easy to use. This system is expected to help reduce bad credit risk and improve decision accuracy.